Collaborative Learning Theory in Overcoming Speaking Anxiety in Undergraduate Students - Nadir La Djamudi; Muslim Muslim; Susiati Susiati (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to explore how female investors' cognitive activity, particularly as it relates to neurotransmitter function, contributes to the emergence of investment bias and influences their financial decision-making behavior. The background to this study is the growing participation of women in the investment world in Indonesia, demonstrating high enthusiasm despite the field being synonymous with numbers, risk, and rational thinking. Methodology: This study focuses on analyzing the role of neurotransmitters as moderating variables in the relationship between cognitive activity and the tendency for investment bias in female investors. While the abstract does not explicitly mention the technical methods used, an interdisciplinary approach combining psychology, neuroscience, and behavioral finance forms the primary foundation of the analysis. Main Findings: The main findings of this study indicate that cognitive activity influenced by neurotransmitter function plays a role in shaping investment bias in female investors. This bias then impacts decision-making patterns, which can differ from those of other investor groups, particularly in the context of risk management and perception of investment opportunities. Novelty/Originality of this study: The uniqueness of this study lies in its approach, which integrates biological and psychological aspects into the study of investment behavior, particularly in women. By focusing on the role of neurotransmitters, this research makes an original contribution to a deeper understanding of the psychobiological basis of financial behavior, which has previously been rarely discussed specifically in a gender context.